Effects of early mycorrhization and colonized root length on low‐soil‐phosphorus resistance of West African pearl millet. Issue 4 (15th June 2016) - Beggi, Francesca; Hamidou, Falalou; Hash, C. Tom; Buerkert, Andreas
Abstract: Phosphorus (P) deficiency at early seedling stages is a critical determinant for survival and final yield of pearl millet in multi‐stress Sahelian environments. Longer roots and colonization with arbuscular mycorrhizal fungi (AMF) enhance P uptake and crop performance of millet. Assessing the genotypic variation of early mycorrhization and its effect on plant growth is necessary to better understand mechanisms of resistance to low soil P and to use them in breeding strategies for low P. Therefore, in this study, eight pearl millet varieties contrasting in low‐P resistance were grown in pots under low P (no additional P supply) and high P (+ 0.4 g P pot −1 ) conditions, and harvested 2, 4, 6, and 8 weeks after sowing (WAS). Root length was calculated 2 WAS by scanning of dissected roots and evaluation with WinRhizo software. AM infection (%) and P uptake (shoot P concentration multiplied per shoot dry matter) were measured at each harvest. Across harvests under low P (3.3 mg Bray P kg −1 ), resistant genotypes had greater total root length infected with AMF (837 m), higher percentage of AMF colonization (11.6%), and increased P uptake (69.4 mg P plant −1 ) than sensitive genotypes (177 m, 7.1% colonization and 46.4 mg P plant −1, respectively). Two WAS, resistant genotypes were infected almost twice as much as sensitive ones (4.1% and 2.1%) and the individual resistant genotypes differed in the percentage of AMF infection. AMF colonization was positively related to final dry matter production in pots, which corresponded to field performance. Early mycorrhization enhanced P uptake in pearl millet grown under P‐deficient conditions, with the genotypic variation for this parameter allowing selection for better performance under field conditions.